Possibility study of areas with potential cultivation of saffron in Kashmar plain using GIS - S. A. Mohammad Alavi Zadeh; Ali Monazzam Esmaeel Pour; Mahmoud Hossein Zadeh Kermani (Zirā̒at va Fanāvarī-i Za̒farān, 2013)
Saffron as the most expensive agriculture and medicinal product of world, is a plant in Consider to aridity resistant has interesting role in social and economical status of arid and semi arid of southern and Razavi Khorasan provinces. The aim of this paper, is determining the suitable area in Saffron cultivation with regards to effective factors. The climatic elements data were obtain from Khorasan Razavi Meteorological Organization for 1989-2012 periods. The topographic data including; relief, slope, aspect and TIN layers extracts from 1: 50000 topographic maps of the region. The land use and vegetation land cover maps were prepared using 1: 50000 maps of National soil and water Research Institute. The spatial analysis facilities of GIS were used for numerical calculation and drawing the requiring maps. A spatial geo database from region was established then spatial and description data entered on this database. Using by AHP software each layer weighted by its importance. Finally, by overlaying analysis in ArcGIS, cultivated area were classified by its capabilities .The results showed that Central and Southern Kashmar plain are the best capabilities for Saffron cultivation that in present statues, these lands specified to dry farming, irrigated farming, semi condense and condense rangelands.